DHZCP Modulates Microglial M1/M2 Polarization via the p38 and TLR4/NF-κB Signaling Pathways in LPS-Stimulated Microglial Cells - Zhou, Lu; Wang, Dongsheng; Qiu, Xinjian; Zhang, Weiru; Gong, Zhicheng; Wang, Yang; Xu, Xia (Frontiers in Pharmacology, 2020)
Intracerebral hemorrhage (ICH) is a disease of significant high rate of morbidity, mortality and disability. Inhibition of inflammation is considered as a potential target for treating ICH. The hallmark of neuroinflammation is the microglia activation. Microglia could polarize into either the classically activated M1(pro-inflammatory) phenotype, exacerbating neuronal damage, or the alternatively activated M2(anti-inflammatory) phenotype, exerting neuroprotection and promoting neuronal recovery. Promoting microglial polarization to the M2 phenotype could possess a more viable strategy for the neuroinflammation treatment. Increasing studies indicated that the method of promoting blood circulation and removing blood stasis exhibited the therapeutic effects on intracerebral hemorrhage. Dahuang Zhechong Pill (DHZCP), a classical recipe of promoting blood circulation and removing blood stasis, has been reported to improve the clinical outcome of intracerebral hemorrhage (ICH). And DHZCP has been shown to exert anti-inflammatory action. However, the detailed anti-inflammatory mechanism of DHZCP on ICH has been rarely investigated. In this study, Firstly, DHZCP inhibited lipopolysaccharide (LPS)-induced M1 phenotype microglia activation. Secondly, DHZCP exerted anti-inflammatory effects, as inferred by that DHZCP inhibited LPS-induced M1 pro-inflammatory cytokines (TNF-α, IL-6), iNOS production and increased M2 anti-inflammatory cytokine (IL-10) production. Thirdly, DHZCP switched microglial M1 to M2 polarization as indicated by the significant increased expression of M2 polarization marker (CD209, CD206) and the marked decreased expression of M1 polarization marker (CD54). Besides, DHZCP inhibited p38 and TLR4/NF-kB signaling activation, as demonstrated by the result that DHZCP inhibited LPS-induced increase of p-p38, TLR4 and nuclear factor kappa B p-65 (NF-kB p-65) protein expression. Taken together, DHZCP modulates microglia M1/M2 polarization via p38 and TLR4/NF-kB signaling pathways to confer anti-inflammatory effects.